Investigation of the psychological, pedagogical and technological adaptation levels of repatriated university students. - Tajibayeva, Zh.; Nurgaliyeva, S.; Aubakirova, K.; Ladzina, N.; Shaushekova, B.; Yespolova, G.; Taurbekova, A. (International Journal of Education in Mathematics, Science, and Technology (IJEMST), 2023)
The International Journal of Education in Mathematics, Science, and Technology (IJEMST) is a peer-reviewed scholarly online journal. This article may be used for research, teaching, and private study purposes. Authors alone are responsible for the contents of their articles. The journal owns the copyright of the articles. The publisher shall not be liable for any loss, actions, claims, proceedings, demand, or costs or damages whatsoever or howsoever caused arising directly or indirectly in connection with or arising out of the use of the research material. All authors are requested to disclose any actual or potential conflict of interest including any financial, personal or other relationships with other people or organizations regarding the submitted work.
Keywords: Repatriated university; students; Psychological adaptation; Technological adaptation; Pedagogy